2018
DOI: 10.5811/westjem.2018.8.38851
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Patients with Ventricular Assist Devices Presenting to an Urban Emergency Department

Abstract: IntroductionLeft ventricular assist device (LVAD) insertion is an increasingly common intervention for patients with advanced heart failure; however, published literature on the emergency department (ED) presentation of this population is limited. The objective of this study was to characterize ED presentations of patients with LVADs with a focus on device-specific complications to inform provider education and preparation initiatives.MethodsThis was a retrospective chart review of all patients with LVADs foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…Broadening this definition to include bleeding and stroke, known complications of continuous-flow LVADs, still accounts for fewer than 1 in 5 LVAD ED presentations. This pattern is similar to that described previously in the literature, and is likely a manifestation of 24-hour care provided by the LVAD team and coordinators at our center and many others, which can facilitate expedited direct admission to LVAD trained units for suspected device-related complications and malfunctions [3] , [4] , [5] . The overall admission rate from the ED in our study is similar to those of prior evaluations, suggesting that the overwhelming majority of LVAD presentations to the ED result in admission [5] , [6] .…”
Section: Discussionsupporting
confidence: 85%
“…Broadening this definition to include bleeding and stroke, known complications of continuous-flow LVADs, still accounts for fewer than 1 in 5 LVAD ED presentations. This pattern is similar to that described previously in the literature, and is likely a manifestation of 24-hour care provided by the LVAD team and coordinators at our center and many others, which can facilitate expedited direct admission to LVAD trained units for suspected device-related complications and malfunctions [3] , [4] , [5] . The overall admission rate from the ED in our study is similar to those of prior evaluations, suggesting that the overwhelming majority of LVAD presentations to the ED result in admission [5] , [6] .…”
Section: Discussionsupporting
confidence: 85%
“…1 Studies have demonstrated that the most common presenting complaint to the emergency department in a patient with a VAD is mucosal bleedingg. 2 While most otolaryngologists are aware of the frequency of epistaxis in this population, to our knowledge the cost of this complication has not been reported. In this case report, we document financial costs of epistaxis in a patient with a VAD over a 16-month period.…”
Section: Introductionmentioning
confidence: 89%
“…Bleeding is the most common reason for ED presentation among patients with left ventricular assist devices, and gastrointestinal bleeding, occurring in 15% to 30% of patients, is the most common source, followed by epistaxis. 17 These patients have several reasons for developing bleeding complications: they are often receiving aspirin and warfarin, the continuousflow state results in arteriovenous malformations, and the pump causes an acquired von Willebrand's disease. [18][19][20][21][22] Gastrointestinal bleeding occurs more…”
Section: Evaluate For Gastrointestinal Hemorrhagementioning
confidence: 99%
“…26,27 Among patients presenting to the ED with pump thrombosis, the average INR in one study was 1.9 compared with 2.2 in those without a thrombosis. 17 Although lactate dehydrogenase level can also be elevated in multiple processes, it can also raise suspicion for pump thrombosis because of the active hemolysis. 11 In the same ED study, 14 patients with pump thrombosis had an average lactate dehydrogenase level of 2,142 units per liter (U/L) compared with 158 patients without thrombosis, who had an average lactate dehydrogenase level of 451 U/L.…”
Section: Blood Testingmentioning
confidence: 99%
See 1 more Smart Citation